EFEK PEMBERIAN SERBUK KUNYIT DALAM PAKAN TERHADAP HEPAR PUYUH JEPANG (Coturnix japonica) - Saraswati, Tyas Rini (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
This study aims to determine the effect of turmeric powder This study aims to determine the effect of turmeric powder supplementation to the liver of Japanese quail (Coturnix japonica). This study uses a completely randomized design. Sixty female quails aged one day (Day Old Quail) were divided into 4 treatment levels of turmeric powder (P0: control; P1: 13.5 mg/quail/day; P2: 27 mg/quail/day; Q3: 54 mg/quail/day). Each treatment used 15 quails. Eat and drink provided ad libitum. The parameters observed were liver weight, hepatocyte diameter at the base, middle, and end, and levels of SGPT and SGOT. The results showed that supplementation of turmeric powder did not affect the weight of the liver, increase in both hepatocytes diameter at the base, middle, and end, as well as decreased levels of SGPT and SGOT blood. Based on the results of this study, the supplementation of turmeric powder quail improves the liver function. Keywords : turmeric, Japanese quail, liver